2015
DOI: 10.1038/srep08342
|View full text |Cite
|
Sign up to set email alerts
|

Extensive load of somatic CNVs in the human placenta

Abstract: Placenta is a temporary, but indispensable organ in mammalian pregnancy. From its basic nature, it exhibits highly invasive tumour-like properties facilitating effective implantation through trophoblast cell proliferation and migration, and a critical role in pregnancy success. We hypothesized that similarly to cancer, somatic genomic rearrangements are promoted in the support of placental function. Here we present the first profiling of copy number variations (CNVs) in human placental genomes, showing an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 58 publications
5
57
3
Order By: Relevance
“…This is a key feature in implantation process and normally functioning trophoblastic cells, and is represented in the most extreme form in multinuclear syncytiotrophoblast layer in the human placenta and in trophoblastic giant cells in mouse37. Consistent with the critical role of endocycle process in the normal placental development and function, our recent study identified an extensive load of somatic structural variants in the human placental genome and the highest fraction of genomic rearrangements was detected in normal pregnancies38. Endoreplication is essential for normal early development in many eukaryotic organisms39 and the role of E2F transcription factors in the involved processes appears to be evolutionarily conserved among mammals and insects40.…”
Section: Discussionsupporting
confidence: 62%
“…This is a key feature in implantation process and normally functioning trophoblastic cells, and is represented in the most extreme form in multinuclear syncytiotrophoblast layer in the human placenta and in trophoblastic giant cells in mouse37. Consistent with the critical role of endocycle process in the normal placental development and function, our recent study identified an extensive load of somatic structural variants in the human placental genome and the highest fraction of genomic rearrangements was detected in normal pregnancies38. Endoreplication is essential for normal early development in many eukaryotic organisms39 and the role of E2F transcription factors in the involved processes appears to be evolutionarily conserved among mammals and insects40.…”
Section: Discussionsupporting
confidence: 62%
“…We have previously shown that the high load of CNVs in the human placental genome arises mainly from somatic duplications9. Notably, the seminal study also demonstrated that placentas from late pregnancy complications such as preeclampsia, gestational diabetes and fetal growth disturbances exhibit significantly lower number of CNVs.…”
Section: Resultsmentioning
confidence: 99%
“…For 50 placental samples profiled for their CNV content in the current and previous study9, also RNA-Seq dataset has been generated2021. In order to assess the functional effect of CNVs on the expression of the involved genes (termed as ‘CNV genes’; n = 2,273 across all samples), we compared their transcript levels with the remaining Ensembl genes, not disrupted by CNVs in any placental samples (‘non CNV genes’; n = 45,156).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations